Mejoramiento genético. Mejoramiento de caracteres. Tolerancia a sequía - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
Studies on drought tolerance at CIAT emphasized validating present screening strategies, and testing modifications that will further improve their efficiency. The evaluation of the screening techniques included the selection of appropriate exptl. design and the study of the interactions among var. and agronomic management. Also, efforts were invested in understanding tolerance mechanisms such as root growth and orientation of leaves. (CIAT)